The Effect of Socio-Demographic Factors on Dental Anxiety of Children Admitted to a Hospital-Setting Pediatric Dental Care Unit - Çiğdem Elbek Çubukçu; İlker Ercan (Güncel Pediatri)
Aim: This study aimed to determine how socio-demographical factors related to dental anxiety of a sample of children who admitted to a hospital-setting dental care unit. Materials and Methods: A total of 305 randomly selected children (aged 7-12 years) who did not have a history of attendance at a dental clinic before, were evaluated for dental anxiety by the Dental Scale (DAS). Socio-demographic data were also obtained from the patients as well as the accompanying parent(s). Results: The mean DAS score was determined 7.7±3.1. The highest DAS score was recorded for drilling (2.3±1.0). There was statistically significant (p<0.01) association between the anxiety level of the children before procedure and their age. 201 parents (66%) had 5 years of formal schooling. A significantly (p<0.001) greater than average proportion of children were from lower class homes. There was no statistically significant (p>0.05) difference between the social class distribution of the children and the type of school attended. Children who were from lower class homes and attended public school, had a lower anxiety level. Conclusion: Children’s level of dental anxiety before their initial visit, may be directly associated with child’s age, the school attended, and parent’s income and education level. However, a positive correlation may not exist between child’s gender and his dental anxiety. (Journal of Current Pediatrics 2008; 6: 53-7)